Faktor-Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Manufaktur Di Bei - Jessica, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effects of firm size, profitability, financial leverage, and liquidity on income smoothing at manufacturing firms listed on Indonesian Stock Exchange during the period of 2015-2017. The data used in this research was secondary data in the form of financial information from the financial statements and annual reports. There were 60 samples of manufacturing companies that have been previously selected using purposive sampling method with total of 180 data for three years. Binary Logistic Regression was used in analyzing the relationship between the independent and dependent variables. This research data was processed using IBM SPSS 23. Results shows that firm size, financial leverage, and liquidity has a significant influence on the practice of income smoothing, while profitability has no significant influence on the practice of income smoothing.